Engineered column treatment of greywater using raw and pyrolyzed coconut husk powder - Taylor, Theodora Sophia; Appiah-Effah, Eugene; Akodwaa-Boadi, Kofi; Obeng, Ernest; Ofei-Quartey, Muriel Naa Lamiokor (Frontiers in Environmental Science, 2023)
Reclaimed water from wastewater has become a prominent water source option to manage water scarcity. This study explores the potential of coconut husk biomass, a common waste material in Ghana, as a valuable low-cost resource for greywater treatment. Engineered column treatment was applied to investigate the influence of pyrolysis and biochar properties of coconut husk biomass waste on greywater treatment. Coconut husk biomass waste was pyrolyzed at 600°C and characterized using SEM, FTIR, and XRD. Three engineered columns with 1) raw coconut husk powder (RCHP), 2) charred coconut husk powder (CCHP), and 3) sand-gravel filters (control setup) were used. A hydrostatic head of greywater with a throughput of 8.0 ml/min and a hydraulic retention time of 45 min was maintained for engineered columns. The SEM image suggested an increased surface area and pores due to the pyrolysis of the husk biomass. RCHP and CCHP contributed to 63% and 95% turbidity removal, respectively. Experimental results showed high removal efficiencies of 71% COD for CCHP. The nitrate removal efficiency of 78.93%, 88.38%, and 28.65% was observed for RCHP, CCHP, and control respectively. The log removal of faecal coliform by CCHP was two orders of magnitude higher than RCHP. Faecal and total coliform removal was 2.87 log units for CCHP. Significant differences were observed between CCHP and RCHP, p < 0.05 for electrical conductivity and total dissolved solids of effluents. CCHP showed a promising potential for greywater treatment. Pyrolyzed coconut husk powder is a promising adsorbent applicable to greywater treatment.